The attitude-behaviour gap in biosecurity: Applying social theories to understand the relationships between commercial chicken farmers' attitudes and behaviours - Pao, Hai-ni; Jackson, Elizabeth; Yang, Tsang-sung; Tsai, Jyan-syung; Hwang, Yi-ting; Sung, Watson H. T.; Pfeiffer, Dirk U. (Frontiers in Veterinary Science, 2023)
Traditionally, it is believed that people’s behaviours align with their attitudes; however, during COVID-19 pandemic, an attitude-behaviour gap in relation to preventive measures has been observed in recent studies. As such, the mixed-methods research was used to examine the relationships between farmers’ biosecurity attitudes and behaviours in Taiwan’s chicken industry based on the cognitive consistency theory. Content analysis of face-to-face interviews with 15 commercial chicken farmers identified their biosecurity responses to infectious disease threats. The results indicated the mismatch of farmers’ attitudes and behaviours towards specific biosecurity measures, in that they act differently than they think. The findings of the qualitative research allowed the research team to conduct the subsequent quantitative, confirmatory assessment to investigate the mismatch of farmers’ attitudes and behaviours in 303 commercial broiler farmers. Survey data were analysed to discover the relationships between farmers’ attitudes and behaviours in relation to 29 biosecurity measures. The results show a mixed picture. The percentage of the farmers who had the attitude-behaviour gap towards 29 biosecurity measures ranged from 13.9% to 58.7%. Additionally, at the 5% significant level, there is an association between farmers’ attitudes and behaviours for 12 biosecurity measures. In contrast, a significant association does not exist for the other 17 biosecurity measures. Specifically, out of the 17 biosecurity measures, the disconnection of farmers’ attitudes and behaviours was observed in three specific biosecurity measures such as using a carcass storage area. Based on a fairly large sample of farmers in Taiwan, this study confirms the existence of an attitude-behaviour gap in context and applies social theories to provide an in-depth understanding of how infectious diseases are managed in the animal health context. As the results demonstrate the necessity of tailoring biosecurity strategies to address the gap, it is time to reconsider the current approach by understanding farmers’ real attitudes and behaviours in relation to biosecurity for the success of animal disease prevention and control at the farm level.